Factors influencing the intention to use digital wallets in Malaysia - Chew, Jian Wei; Parveen Kaur, Arjan Singh; Siew, Xue Yean; Tan, Hui Yun; Tan, Yu Zhen (2021)
Digital wallets have been applicable in Malaysia but only 8% of population utilized them (Abdullah, Fauziah and Daud, 2020). As this technology usage is growing in Malaysia, this paper is to discover the reasons influencing Malaysians’ intention to apply digital wallets. Additionally, this research will be using the extended Theory of Planned Behaviour model by including perceived security as an independent variable which showcase the uniqueness of this study. A total of 300 Malaysians were selected as respondents in this paper through snowball sampling and the data collected were analysed using Statistical Package for Social Sciences. In this study, implications have also been indicated along with limitation and recommendation being figured out as references for future businessmen, researchers and others.